Degradação de substâncias de relevância ambiental por processos oxidativos e redutivos com monitoramento por espectrometria de massas com ionização electrospray - Ana Paula Fonseca Maia de Urzedo (2008)
Firstly, the degradation of the insecticides Thiamethoxam, Imidacloprid and Methomyl in aqueous solutions by a number of processes was studied. It was verified that although the UV radiation was highly efficient in promoting the degradation of Thiamethoxam, the combined systems, i. e. UV/catalyst and UV/US/catalyst (catalyst = Fe2O3 or Fe3O4), showed to be much less efficient. Other systems, i. e. Feº, Feº/Fe3O4, and Feº/Fe3O4/H2O2, were also able to cause the degradation of the insecticides Thiamethoxam and Imidacloprid in acidic aqueous solution (pH = 2). In addition, the experimental data revealed that the Feº/Fe3O4 and Feº/Fe3O4/H2O2 systems lead to the reduction and oxidation of both insecticides, respectively. Finally, the insecticide Methomyl reached 100% of degradation when submitted to the UV radiation. The degradation of prototype food dyes by a number of oxidative processes was also investigated. The UV/H2O2, O3, and NaClO systems were able to promote a quick and intense discoloration of the aqueous solutions of such dyes. The analyses of TOC (total organic carbon) revealed that the degradation processes were not able to promote a complete mineralization of pesticides and dyes. The degradation products formed under such assorted conditions were characterized via electrospray ionization mass (and tandem mass) spectrometry, which thus demonstrated to be a suitable technique to monitor degradation processes in aqueous solution.